Recirculation of Giardia lamblia Assemblage A After Metronidazole Treatment in an Area With Assemblages A, B, and E Sympatric Circulation - Fantinatti, Maria; Lopes-Oliveira, Luiz Antonio Pimentel; Cascais-Figueredo, Tiara; Austriaco-Teixeira, Phelipe; Verissimo, Erika; Bello, Alexandre Ribeiro; Da-Cruz, Alda Maria (Frontiers in Microbiology, 2020)
Giardia lamblia is an intestinal protozoan subdivided into eight assemblages, labeled alphabetically from A to H. Assemblages A, B, and E infect humans and can have a sympatric circulation. We investigated the assemblage recirculation in children living within a high prevalence area of Giardia infection. One hundred and ninety-four children were evaluated and 85 tested positive for Giardia by PCR. These infected individuals were recruited, treated with metronidazole, and then reexamined for infections at 20 and 40 days after treatment that included PCR and the genotyping was performed by sequencing beta-giardin and glutamate dehydrogenase gene targets. Giardia assemblages A (n=43), B (n=21), E (n=17) and A/E (n=4) were identified in infected children. Assemblage A was found in all reoccurrences of infection, including four that had been infected by assemblages B and E. Since both persistence and reinfection could account for the results, the level of nucleotide homology was determined before and after treatment. Most suggested that reinfections were by the same strain, but four presented a distinct genotypic profile. The results suggest that the differences in the genotypic profiles were due to reinfections, which appear to occur with frequency in high Giardia burden areas and soon after the end of therapy. It is not yet possible to define whether the recurrent cases were related to parasite resistance. However, the evidence of rapid reinfections and ready availability of treatment raises the potential for creating resistant strains. This highlights the need to address how Giardia's burden is maintained within high prevalence areas.